2015
DOI: 10.1002/ece3.1536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of theEpichloëfungal endophyte symbiosis withSchedonorus pratensison host grass invasiveness

Abstract: Initial studies of grass–endophyte mutualisms using Schedonorus arundinaceus cultivar Kentucky-31 infected with the vertically transmitted endophyte Epichloë coenophiala found strong, positive endophyte effects on host-grass invasion success. However, more recent work using different cultivars of S. arundinaceus has cast doubt on the ubiquity of this effect, at least as it pertains to S. arundinaceus–E. coenophiala. We investigated the generality of previous work on vertically transmitted Epichloë-associated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(137 reference statements)
0
7
0
Order By: Relevance
“…The site was treated twice with glyphosate herbicide (Roundup, St. Louis, MO, U.S.A.) and cultivated and leveled with a Blecavator (Specialized Turf Equipment Company, Anderson, SC, U.S.A.) to create homogeneous bare soil conditions prior to seeding. Mean daily growing season temperatures (17.03 ± 0.21 ∘ C [SE]) and mean weekly total precipitation (15.86 ± 1.40 mm [SE]) for the area were similar among all study years (Shukla et al 2015).…”
Section: Experimental Designmentioning
confidence: 99%
“…The site was treated twice with glyphosate herbicide (Roundup, St. Louis, MO, U.S.A.) and cultivated and leveled with a Blecavator (Specialized Turf Equipment Company, Anderson, SC, U.S.A.) to create homogeneous bare soil conditions prior to seeding. Mean daily growing season temperatures (17.03 ± 0.21 ∘ C [SE]) and mean weekly total precipitation (15.86 ± 1.40 mm [SE]) for the area were similar among all study years (Shukla et al 2015).…”
Section: Experimental Designmentioning
confidence: 99%
“…However, it is not uncommon to see the same authors’ positions shifting through time (e.g. mutualism : Newman et al, 2003, Ryan et al, 2014, Shukla et al, 2015, Bastías et al, 2018), ( unclear/continuum/admits possibility : Hunt and Newman, 2005, Rasmussen et al, 2007, Antunes et al, 2008).…”
Section: Figure A1mentioning
confidence: 99%
“…At the time the meta-analysis was performed, the preponderant hypothesis was that fungal alkaloids produced by endophyte symbionts which have shown deterrent effects on herbivores (see e.g., Clay 1988;Schardl et al 2007), would have a direct inhibitory effect on litter decomposition. However, as observed for the effects of endophytes on plant-herbivore interactions (Saikkonen et al 2010(Saikkonen et al , 2013aUeno et al 2016;Shukla et al 2015), effects on decomposition have proven to be highly variable with negative, neutral, or positive results depending on host species, partners' genotypes, and ecological conditions (Omacini et al 2004;Lemons et al 2005;Siegrist et al 2010;Gundel et al 2016;Mikola et al 2016). Apart from the alkaloids, endophytes have been associated with changes in plant biomass quality that could be also linked to litter decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…With the same grass species, Lemons et al (2005) found that the exclusion of meso-invertebrates shifted the endophyte effect from decreasing to increasing the rate of litter decomposition. However, endophyte influence on invertebrates (although not necessarily involved in decomposition) associated to host plants has been variable depending on grass species and genotype, and the ecological conditions (see e.g., Rudgers and Clay 2008;Vesterlund et al 2011;Popay and Jensen 2005;Shukla et al 2015). Studies have revealed that symbiosis with leaf fungal endophytes affects abundance and structure of the soil microbial community associated with the rhizosphere of tall fescue plants (Buyer et al 2011;Rojas et al 2016).…”
Section: Introductionmentioning
confidence: 99%